2016
DOI: 10.1186/s13054-016-1221-9
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of functional outcome in patients with convulsive status epilepticus: the END-IT score

Abstract: BackgroundPrediction of the functional outcome for patients with convulsive status epilepticus (CSE) has been a challenge. The aim of this study was to characterize the prognostic factors and functional outcomes of patients after CSE in order to develop a practicable scoring system for outcome prediction.MethodsWe performed a retrospective explorative analysis on consecutive patients diagnosed with CSE between March, 2008 and November, 2014 in a tertiary academic medical center in northwest China. The modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
113
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(116 citation statements)
references
References 43 publications
1
113
1
1
Order By: Relevance
“…First of all, there was no significant relationship between age (with median age of 25 [interquartile range 18-36] in our study) and DRE development, which might imply that age did not play a determinant role in DRE development among survivors who usually were younger. Second, the presence of NCSE in coma or generalized convulsive seizures at onset was reported to be independently associated with a high risk of death and poor functional outcome [5,17]. However, among survivors of SE, NCSE was not found to correlate pronouncedly with DRE development in our study.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…First of all, there was no significant relationship between age (with median age of 25 [interquartile range 18-36] in our study) and DRE development, which might imply that age did not play a determinant role in DRE development among survivors who usually were younger. Second, the presence of NCSE in coma or generalized convulsive seizures at onset was reported to be independently associated with a high risk of death and poor functional outcome [5,17]. However, among survivors of SE, NCSE was not found to correlate pronouncedly with DRE development in our study.…”
Section: Discussioncontrasting
confidence: 71%
“…Accordingly, many studies have investigated the risk factors of mortality and morbidity after SE, and found that age, etiology, seizure type, consciousness, and albumin level were early predictors [3][4][5]. SE is also often followed by unprovoked seizures, although whether epileptogenesis is associated with SE per se or with other underlying brain illness remains in dispute.…”
Section: Introductionmentioning
confidence: 99%
“…The median CBI in the GOS 1-3 group was significantly higher than in GOS >3 group (4 [3-6] and 3[2][3][4] [median, interquartile range], respectively, P = .006). For continuous CBI, the RR value is interpreted as a change in event probability for a one-level increase in CBI.…”
mentioning
confidence: 99%
“…8 A few studies report that mortality in SE might be related to systemic complications in 12%-50% of the cases. [2][3][4] We lack tools to evaluate total complication burden and its effects on outcome. [2][3][4] We lack tools to evaluate total complication burden and its effects on outcome.…”
mentioning
confidence: 99%
“…10 Of the underlying etiologies of SE, encephalitis was chosen as an evaluating dimension in END-IT due to it being the most frequent underlying etiology, 21-23 as well as being determined to be an independent predictor in this study. Independent risk factors, that is, predictor variables, were identified using backward stepwise multivariate logistic regression.…”
Section: Key Pointsmentioning
confidence: 99%